The Effect of Work Safety Climate and Work Safety Knowledge on Work Safety Behavior with Work Safety Motivation as an Intervening Variable - Muhammad Miftahul Maulidy; Intan Ratnawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to analyze how much influence the variables of work safety climate and work safety knowledge have on work safety behavior with work safety motivation as an intervening variable for health workers at RSU Asy-Syifa Sambi Boyolali. The data used in this study is primary data derived from the distribution of research questionnaires. The population in this study were health workers at Asy-Syifa Sambi Boyolali General Hospital, both permanent and non-permanent employees, totaling 130 people. The sample in this study was the entire population mentioned above, namely 130 people. The sampling technique used in this research is the census. This study used the Structural Equation Modeling (SEM) analysis technique with the AMOS 24.0 analysis tool. The findings show that work safety climate has a positive effect on work safety behavior, work safety knowledge has a positive effect on work safety behavior, work safety climate has a positive effect on work safety motivation, work safety knowledge has a positive effect on work safety motivation, work safety motivation has a positive effect on work safety behavior, work safety climate has a positive and significant effect on work safety behavior through work safety motivation, work safety knowledge has a positive and significant effect on work safety behavior through work safety motivation. This study shows that companies must establish a good work safety climate and work safety knowledge for employees so that they are able to improve work safety behavior both directly and through intervening work safety motivation variables.